Scientific bridges between Cuba and the United States - Arencibia-Jorge, Ricardo; Corera-Alvarez, Elena; Vega-Almeida, Rosa Lidia (Revista Cubana de Información en Ciencias de la Salud, 2017)
Political differences between the governments of Cuba and the United States after 1959 have left a deep trace in multiple generations of both countries, including scientists. In fact, lack of scientific bridges between Cuba and the United States is a statement widely assimilated by public opinion. The U.S. government embargo affected all the spheres of Cuban life, and Science was not an exception. However, scientific interactions never have been in a dead point. The main aim of this brief communication is to reveal the characteristics of these scientific relations, and to confirm the increase of links between the two scientific communities from a bibliometric perspective. Scopus was used as data source. SCImago Institutions Rankings, a Scopus-based tool, was used to analyze leadership and collaboration patterns. Both countries exhibited similarities in association strategies for Research & Development activities, and revealed relative independence from international links. However, the United States was the fourth scientific partner of Cuban institutions, and international collaboration between Cuban and American scientists increased during the entire study period. Well-established research networks were identified. Enhancement of research alliances in the new political context should be expected.